Carbon Storage and Fluxes within Freshwater Wetlands: a Critical Review - Kayranli, Birol; Scholz, Miklas; Mustafa, Atif; Hedmark, Åsa (Wetlands (Wilmington, N.C.), 2010)
We critically review recent literature on carbon storage and fluxes within natural and constructed freshwater wetlands, and specifically address concerns of readers working in applied science and engineering. Our purpose is to review and assess the distribution and conversion of carbon in the water environment, particularly within wetland systems. A key aim is to assess if wetlands are carbon sinks or sources. Carbon sequestration and fluxes in natural and constructed wetlands located around the world has been assessed. All facets of carbon (solid and gaseous forms) have been covered. We draw conclusions based on these studies. Findings indicate that wetlands can be both sources and sinks of carbon, depending on their age, operation, and the environmental boundary conditions such as location and climate. Suggestions for further research needs in the area of carbon storage in wetland sediments are outlined to facilitate the understanding of the processes of carbon storage and removal and also the factors that influence them.